The Nigeria publics: integrating non-modern and modern systems of communication for community development (2018)
The need to convey development messages in Nigeria makes it necessary to integrate indigenous and exogenous media, or non-modern and modern systems of communication. This strategy will make development messages easily accessible and comprehensible by different Nigerian publics, a mechanism for eliminating discrimination and alienation of particular communities from development messages. The paper argues that the converging indigenous, traditional and new media platforms would promote the spread of, exposure and response to development ideas by the Nigerian dichotomized audience as well as influence human knowledge, attitude and behaviour. Integrating media messages would ensure participation of diverse communities in development processes despite people’s socioeconomic and residential background. In summary, the meaning of the message should determine the medium of that message. The paper identifies sociocultural context as a determinant of development communication and describes the importance of media convergence to community development. From the viewpoint of development, the integration of non-modern and modern systems of communication is complementary, mutually reinforcing rather than mutually exclusive. This technique has implications for communication networking and information acquisition. The paper contributes to the general body of knowledge on the efficacy of converged media for community development in Nigeria and sub-Saharan Africa.